Later Age at Onset of Independent Walking Is Associated With Lower Bone Strength at Fracture‐Prone Sites in Older Men. (27th March 2017) - Ireland, Alex; Muthuri, Stella; Rittweger, Joern; Adams, Judith E; Ward, Kate A; Kuh, Diana; Cooper, Rachel
ABSTRACT: Later age at onset of independent walking is associated with lower leg bone strength in childhood and adolescence. However, it is unknown whether these associations persist into older age or whether they are evident at axial (central) or upper limb sites. Therefore, we examined walking age obtained at age 2 years and bone outcomes obtained by dual‐energy X‐ray absorptiometry (DXA) and peripheral quantitative computed tomography (pQCT) scans at ages 60 to 64 years in a nationally representative cohort study of British people, the MRC National Survey of Health and Development. It was hypothesized that later walking age would be associated with lower bone strength at all sites. Later independent walking age was associated with lower height‐adjusted hip (standardized regression coefficients with 95% confidence interval [CI] –0.179 [–0.251 to –0.107]), spine (–0.157 [–0.232 to –0.082]), and distal radius (–0.159 [–0.245 to –0.073]) bone mineral content (BMC, indicating bone compressive strength) in men (all p  < 0.001). Adjustment for covariates partially attenuated these associations, primarily because of lower lean mass and adolescent sporting ability in later walkers. These associations were also evident for a number of hip geometric parameters (including cross‐sectional moment of inertia [CSMI], indicating bone bending/torsional strength) assessed by hip structural analysis (HSA) from DXA scans. Similar height‐adjusted associations were also observed in women for several hip, spine, and upper limb outcomes, although adjustment for fat or lean mass led to complete attenuation for most outcomes, with the exception of femoral shaft CSMI and spine bone area (BA). In conclusion, later independent walking age appears to have a lifelong association with bone strength across multiple skeletal sites in men. These effects may result from direct effects of early life loading on bone growth and mediation by adult body composition. Results suggest that late walking age may represent a novel risk factor for subsequent low bone strength. Existing interventions effective in hastening walking age may have positive effects on bone across life. © 2017 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals Inc.